On the experimental study of a concentric wave energy array adapted to an offshore floating platform - Kamarlouei, Mojtaba (2019)
Experimental results of the dynamics of a small scale concentric wave energy converter array adapted to a floating offshore platform are presented. A small scale prototype is tested without and with twelve conical heaving point absorbers. The free decay and regular wave tests are carried out in an ocean basin to understand the hydrodynamic interactions between various elements of the floating offshore platform and wave energy converter array. Meanwhile, the heave motions of the buoys are observed in regular waves with and without dampers for the initial estimation of power take-off damping as a pitch control module. The results show the improvements in heave, pitch, and roll performance of the platform due to the interaction between the buoys and platform.